Health economics of targeted intraoperative radiotherapy (TARGIT-IORT) for early breast cancer: a cost-effectiveness analysis in the United Kingdom. Issue 8 (17th August 2017) - Vaidya, Anil; Vaidya, Param; Both, Brigitte; Brew-Graves, Chris; Bulsara, Max; Vaidya, Jayant S
Abstract : Objective: The clinical effectiveness of targeted intraoperative radiotherapy (TARGIT-IORT) has been confirmed in the randomised TARGIT-A (targeted intraoperative radiotherapy-alone) trial to be similar to a several weeks' course of whole-breast external-beam radiation therapy (EBRT) in patients with early breast cancer. This study aims to determine the cost-effectiveness of TARGIT-IORT to inform policy decisions about its wider implementation. Setting: TARGIT-A randomised clinical trial (ISRCTN34086741 ) which compared TARGIT with traditional EBRT and found similar breast cancer control, particularly when TARGIT was given simultaneously with lumpectomy. Methods: Cost-utility analysis using decision analytic modelling by a Markov model. A cost-effectiveness Markov model was developed using TreeAge Pro V.2015. The decision analytic model compared two strategies of radiotherapy for breast cancer in a hypothetical cohort of patients with early breast cancer based on the published health state transition probability data from the TARGIT-A trial. Analysis was performed for UK setting and National Health Service (NHS) healthcare payer's perspective using NHS cost data and treatment outcomes were simulated for both strategies for a time horizon of 10 years. Model health state utilities were drawn from the published literature. Future costs and effects were discounted at the rate of 3.5%. To address uncertainty, one-way and probabilistic sensitivity analyses were performed. Main outcome measures: Quality-adjusted life-years (QALYs). Results: In the base case analysis, TARGIT-IORT was a highly cost-effective strategy yielding health gain at a lower cost than its comparator EBRT. Discounted TARGIT-IORT and EBRT costs for the time horizon of 10 years were £12 455 and £13 280, respectively. TARGIT-IORT gained 0.18 incremental QALY as the discounted QALYs gained by TARGIT-IORT were 8.15 and by EBRT were 7.97 showing TARGIT-IORT as a dominant strategy over EBRT. Model outputs were robust to one-way and probabilistic sensitivity analyses. Conclusions: TARGIT-IORT is a dominant strategy over EBRT, being less costly and producing higher QALY gain. Trial registration number: ISRCTN34086741; post results